Case Report: Giant axillary lipoma in an infant - Ren, Haiyang; Lv, Haoqiang; Wang, Chuanjun; Liu, Hao; Liu, Xiurui; Wei, Hua; Tian, Ping (Frontiers in Pediatrics, 2024)
Lipoma is a benign mesenchymal tissue tumor composed of mature adipose cells, which is most common in adults and rarely seen in children. The clinical data of an infant with axillary giant lipoma admitted to our hospital were analyzed. A 12-month old girl presented with a large right axillary mass. Imaging examination considered mesenchymal tissue tumor, and postoperative pathology confirmed lipoma.